The "Notorious Personalities" Collection in the Bălți University Library (Bibliouniversitas@ABRM.md, 2025)
The article describes and promotes the Notorious Personalities book collection from the Scientific Library of USARB. The following are reviewed: the history of the appearance of this collection, the first debut volume, the launch of the volumes, their promotion in various cultural and scientific activities, their purpose, purpose, and impact. The prominent personalities of the scientific and cultural life of Bessarabia are determined and identified.
Keywords: USARB Scientific Library collection